A Field Perspective on Supplementation of Specific Critical Minerals in CrossbredCattle with Reproductive Disorders - B. Devasena, B. Devasena; J.V. Ramana; I.J. Reddy; P. Eswara Prasad; J. Rama Prasad (Indian Journal of Animal Nutrition, 2025)
ABSTRACT A field experiment was conducted in two adopted villages (Pudipatla 13.6087° N, 79.3620° E and N V Palle 13.48835° N, 79.32755° E ) of Chittoor district of Andhra Pradesh to study the effect of supplementation of deficient minerals in crossbred cattle with reproductive inefficiency. Crossbred cattle (40) with different reproductive problems were selected from two adopted villages. The Area Specific Mineral Mixture (ASMM) prepared by the department of Animal Nutrition, SVVU, Tirupati, having specific deficient minerals (Ca, P, Cu and Zn) was supplemented (40g) to selected animals for 90 days. Blood samples were collected from animals before and after supplementation of ASMM and analysed for different minerals (Ca, P, Cu and Zn) and hormones (estrogen and progesterone). Plasma Ca content of repeat breeding cows (8.03 Vs 9.45 mg %) and anoestrous heifers (7.68 Vs 8.86 mg %) indicated significant (P < 0.05) improvement. In anoestrous heifers P (4.10 Vs 5.49 mg %) and Cu (0.52 Vs 0.88 ppm) showed significant (P < 0.05) elevation in plasma. While Zn content (ppm) in plasma improved significantly (P < 0.05) in anoestrous cows, repeat breeder cows as well as anoestrous heifers. The estrogen content of repeat breeding cows (12.68 Vs 16.42 pg/ml) and anoestrous heifers (13.38 Vs 17.19 pg/ml) as well as progesterone content of repeat breeding cows (1.68 Vs 2.31 ng/ml) and anoestrous heifers (0.88 Vs 1.73 ng/ml) indicated significant (P < 0.05) elevation in plasma of the crossbred animals under study. Among the animals under study, 61.5% of anoestrous cows, 62.5% of repeat breeder cows and 63.6% of anoestrous heifers responded to supplementation. On an average 62.5% of animals under study responded to supplementation of ASMM. It can be concluded that, supplementation of specific deficient minerals in the form of ASMM resulted in improved mineral status and hormonal profile of animals thereby improving the reproductive efficiency in crossbred cattle.